A novel F13A1 gene mutation (Arg208Pro) in a Chinese patient with factor XIII deficiency. Issue 6 (September 2022) - Xie, Haixiao; Wang, Mingshan; Jin, Yanhui; Li, Xiaolong; Jiang, Shuting; Yang, Lihong
Abstract : The objective of the study was to analyse a novel F13A1 gene mutation in a Chinese patient with factor XIII (FXIII) deficiency and explore the molecular mechanism. Pedigree investigation, clinical diagnosis, phenotypic and genetic analysis were conducted. The F13A1 gene was amplified by PCR and directly sequenced. Online bioinformatics software was needed to analyse the mutation. A novel mutation c.515G>C (p.Arg208Pro) in exon 4 was found in the proband. Protein Arg208 is conserved highly among homologous species. Bioinformatics software showed that Arg208Pro mutation might affect the protein function. We preliminarily believed the mutation Arg208Pro was responsible for the decrease FXIII level. We reported a novel mutation in the F13A1 gene, which can flesh out the mutant library.